Poster: A New Management Model for An Ancient Risk - Yu, Lawrence (New Zealand Journal of Health and Safety Practice, 2024)
Most finely divided combustible materials are hazardous. When suspended in air and ignited, they can cause severe explosions. This phenomenon has been known for over 200 years. The first recorded dust explosion occurred on December 14, 1785, at a flower dust explosion in a warehouse in Turin, Italy. The entire industrial spectrum, including agricultural, chemical, metallurgical, mining, plastics, and woodworking industries, continues to be plagued by this problem. Although the basic principles for controlling dust explosions have been understood for many years, knowledge is becoming increasingly sophisticated as incidents continue to occur. The International Network of Safety and Health Practitioners Organisations framework requires health and safety practitioners to have some knowledge of explosions. This poster identifies some accessible sources of information that could be used by practitioners.